Antioxidant capacity, total phenolics and nutritional content in selected ethiopian staple food ingredients. (18th June 2013) - Forsido, Sirawdink Fikreyesus; Rupasinghe, H. P. Vasantha; Astatkie, Tess
Abstract: The total antioxidant capacity, total phenolics content (TPC) and nutritional content of five types of enset ( Enset ventricosum ) flour in comparison with four staples (teff [ Eragrostis tef ], wheat, corn and tapioca) were evaluated. Teff, corn and "amicho" (corm of enset) had the highest ferric reducing antioxidant power (FRAP). The FRAP and TPC of teff (1.8 mmol Trolox equivalence/100 g dry matter (DM) and 123.6 mg gallic acid equivalent/100 g DM, respectively) were over 4-fold larger than the lowest obtained from "bulla" (dehydrated juice of pseudostem of enset). Corn had the lowest IC50 value of 1, 1-diphenyl-2-picrylhydrazyl radical scavenging (10.27 mg DM mL −1 ). Teff had the highest crude fat content (3.71%) and some mineral profile (P, Mg, Mn and Cu). Enset products had higher fiber, Ca, K, Mg and Mn content as compared to wheat and corn. Ethiopian staple teff has a potential for developing value-added food products with nutritional and health benefits.